PERMIAN FUSULINID ASSEMBLAGES AND STRATIGRAPHY OF THE TRANSCAUCASIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
The Permian sequence of the Transcaucasia, which comprises the Davaly, Asni, Gnishik, Arpa, Khachik, and Akhura Formations, is described. A precise dating of the formations based on the analysis of fusulinid assemblages is also provided. The Davaly Formation corresponds to the Bolorian Stage of the Lower Permian (Cisuralian); the Asni Formation corresponds to the Kubergandian Stage, and to the lower half of the Murgabian Stage of the Middle Permian (Guadalupian); the Gnishik Formation corresponds approximately to the upper half of the Murgabian Stage; and the Arpa and Khachik Formations represent the entire Midian Stage of the Middle Permian. Only the uppermost Chanakhchy Beds of the Khachik Formation are referred to the upper series of the Permian (Lopingian), based on the latest proposal of the International Subcommission on Permian Stratigraphy concerning series boundaries. The Akhura Formation encompasses the Dzhulfian and Dorashamian Stages of the Upper Permian. Refined correlations between the Permian sequence of the Transcaucasia and the most complete Permian sequences of the Tethyan region (Central Iran, southestern Pamirs, South China, Japan ) are presented. The transgressive overlapping of the Permian deposits is recorded in these areas, similar to the Transcaucasia. Although the transgression began during the Bolorian, it reached the widest extent in the Kubergandian and therefore, in most sections the transgressive series begins with deposits of Kubergandian age. The Middle and Upper Permian deposits of the Transcaucasia, Iran, and southern Turkey belonged to a single carbonate platform. Similar extensive carbonate platforms are recorded in the southern parts of Afghanistan and China. A change in the sedimentary regime was recorded in all these platforms at the boundary between the Guadalupian and Lopingian epochs. The Guadalupian time was marked by the intensive accumulation of biolitithic and detrital limestones produced by benthic organisms, mainly algae and foraminifers, whereas in the Lopingian time, carbonate and clayey micritic deposition dominated, and the role of nectonic-planctonic and nectonic organisms, such as cephalopods and conodonts, increased. The sedimentation change was abrupt and caused probably by the short-term post-Midian regression. The change resulted in a significant biotic crisis when larger fusulinids, goniatitids and agoniatitids, tabulate corals, most rugose corals and other organisms became entirely extinct. These events marked the onset of the Late Permian "Great Extinction", which ended at the Permian/Triassic boundary. Nine paleontological plates show the main fusulinid assemblages. Nine new species are described: Codonofusiella (?) vediensis, Chalaroschwagerina davalensis, Pseudofusulina arpaensis, P. araxensis, P. pjatakovae, Rugosochusenella davalensis, Misellina (Misellina) caucasica, Cancellina armenica, and Sumatrina vediensis.